Transformation Analysis of Human Resources Development in Dr. Pallemai Tandi Regional Public Hospital, Palopo City - Umar, Fitriana; Ayuandira, Ririn; Abri Hadi (Sean Institute, 2025)
In today's digital era, hospitals face great challenges in adapting their service systems and internal management to advances in information technology. One of the crucial aspects affected is the development of human resources (HR), which must be able to adapt to digital changes quickly and effectively. This study aims to determine the effect of digital transformation on HR development at RSUD dr. Palemmai Tandi Palopo City. The research method used is quantitative method with simple linear regression approach. The number of respondents in this study were 51 people selected through total sampling technique. The results showed that digital transformation has a positive and significant effect on HR development, with a regression coefficient value of 0.765 and a significance value of <0.001. The R square value of 0.589 shows that digital transformation explains 58.9% of the variation in HR development. Thus, the higher the level of digital transformation, the higher the HR development in the hospital environment.